STRATEGI PENGUATAN MICROFINANCE SYARIAH BERBASIS EKONOMI KELEMBAGAAN - Darwanto Darwanto (Inferensi Jurnal Penelitian Sosial Keagamaan, 2014)
The purpose of this study is to obtain an overview of the sharia microfinance issues, sharia microfinance solutions to solve problems, and institutions strategies for strengthening sharia microfinance. The method used in this study is a qualitative analysis method using the tool Analytical Network Process (ANP) is used to find the priority of problems, solutions and strategies for improvement of sharia microfinance institutions. The results of studies suggest that the improvement in sharia microfinance institutions have 4 aspects, those are the problems of the human resource aspects (SDI), infrastructure aspects, market aspects, and management aspects. Aspect of the priority issues in the sharia microfinance institutional improvement is a human resources (SDI), while the improvement solution of sharia microfinance institutional is an aspect of human resources (SDI) as well. Then the strategy which becomes a priority in the improvement of sharia microfinance institutions is the optimization of the board of sharia (DPS)